Adaptasi Sosial Masyarakat terhadap Budaya Living Islam di Pondok Pesantren Al Fatah Temboro - Ananda Nur Husain Al-Hafifi; Destina Eka Aprilia; Najwa Salsabila Agustina; Sayyid Arkan Nizami; Al Fathir Rahman Zulkarnain; Achmad Farid; Andy Hadiyanto (Simpati, 2026)
This study aims to analyze the social adaptation of the community to the Living Islam culture in the environment of Al Fatah Temboro Islamic Boarding School. This study employed a qualitative approach with field research as its research design. Data were collected through interviews, observation, and documentation involving two main informants: an Islamic teacher who actively participates in the boarding school environment and a native resident of Temboro. The data were analyzed through data reduction, data display, and conclusion drawing, while data credibility was strengthened through source and technique triangulation. The findings show that the Living Islam culture in Temboro is reflected in congregational worship, Islamic preaching activities, religious traditions during Ramadan and Muharram, Qur’an reading practices, and Islamic dress. The community adapts through habituation, social interaction, role models provided by boarding school figures, and participation in boarding school activities. This adaptation encourages changes in community life toward a more religious environment, structures public visual identities, reshapes local livelihoods, and strengthens social relations based on structural-functional stability between the boarding school and local residents. The study indicates that Islamic boarding schools play an important role as centers of education, Islamic preaching, socio-economic restructuring, and socio-religious cultural formation.